Selective and High‐Performance Electrochemical Sensor for Cadmium Ions Based on Intimate Binary Spinel CoMn2O4 Nanostructures. Issue 45 (2nd December 2019) - Balaji, Ramachandran; Renganathan, Vengudusamy; Chen, Shen‐Ming; Singh, Vyoma
Abstract: Due to an exponential increase in the industrialization and processing of raw materials had duly resulted in the rapid contamination of heavy metals in the land and water. For the sustainable ecosystem and high standard human life, an analytical quantification of cadmium in drinking water, chocolates, drinks and other environmental systems is of greater importance. The current public welfare sector is in high demand for the rational design and fabrication of the economical, user friendly and point of care device for the sensing of toxic heavy metal cadmium in water. In combination with high sensing performance, the sensor must also be highly robust, selective and good reproducibility upon detection. With the understanding of the facts, we report a novel and direct electrochemical based sensing of cadmium ions based on CoMn2 O4 nanostructures in the water. Linear Sweep Voltammetry (LSV) was employed for the investigation of cadmium ions detection at a lower concentration for the unswerving electrochemical sensing on a CoMn2 O4 nanostructure matrix. Since, the LSV works on the unidirectional sweep principle it eliminates the possible interference of other elements during the reverse sweep. This analytical process is very reliable, low cost and ultrasensitive upon others. The fabricated CoMn2 O4 nanostructure modified electrode displayed good sensitivity 3.3454 μAμM −1 cm −2 and limit of detection 0.0124 μM with a linear range varying up to 0.1 to 761 μM. Abstract : The high increase in industrialization had resulted in heavy metal contamination in environment which has encouraged us to develop a high‐performance electrochemical sensor for cadmium ions in drinking water based on CoMn2 O4 Nanostructures. The LSV technique was used for investigation where we obtained an impressive sensitivity 3.3454 μAμM −1 cm −2 and limit of detection 0.0124 μM with linear range varying up to 0.1 to 761 μM. Thus, CoMn2 O4 Nanostructures could serve as an answer for low concentration sensing of heavy metals.